Alteration of a Shiga toxin-encoding phage associated with a change in toxin production level and disease severity in Escherichia coli. Issue 2 (23rd February 2023) - Miyata, Tatsuya; Taniguchi, Itsuki; Nakamura, Keiji; Gotoh, Yasuhiro; Yoshimura, Dai; Itoh, Takehiko; Hirai, Shinichiro; Yokoyama, Eiji; Ohnishi, Makoto; Iyoda, Sunao; Ogura, Yoshitoshi; Hayashi, Tetsuya
Abstract : Among the nine clades of Shiga toxin (Stx)-producing Escherichia coli O157:H7, clade 8 is thought to be highly pathogenic, as it causes severe disease more often than other clades. Two subclades have been proposed, but there are conflicting reports on intersubclade differences in Stx2 levels, although Stx2 production is a risk factor for severe disease development. The global population structure of clade 8 has also yet to be fully elucidated. Here, we present genome analyses of a global clade 8 strain set ( n =510), including 147 Japanese strains sequenced in this study. The complete genome sequences of 18 of the 147 strains were determined to perform detailed clade-wide genome analyses together with 17 publicly available closed genomes. Intraclade variations in Stx2 production level and disease severity were also re-evaluated within the phylogenetic context. Based on phylogenomic analysis, clade 8 was divided into four lineages corresponding to the previously proposed SNP genotypes (SGs): SG8_30, SG8_31A, SG8_31B and SG8_32. SG8_30 and the common ancestor of the other SGs were first separated, with SG8_31A and SG8_31B emerging from the latter and SG8_32 emerging from SG8_31B. Comparison of 35 closed genomes revealed the overall structure of chromosomes and pO157 virulence plasmids and the prophage contents to be well conserved. However, Stx2a phages exhibit notable genomic diversity, even though all are integrated into the argW locus, indicating that subtype changes in Stx2a phage occurred from the γ subtype to its variant (γ_v1) in SG8_31A and from γ to δ in SG8_31B and SG8_32 via replacement of parts or almost entire phage genomes, respectively. We further show that SG8_30 strains (all carrying γ Stx2a phages) produce significantly higher levels of Stx2 and cause severe disease more frequently than SG8_32 strains (all carrying δ Stx2a phages). Clear conclusions on SG8_31A and SG8_31B cannot be made due to the small number of strains available, but as SG8_31A (carrying γ_v1 Stx2a phages) contains strains that produce much more Stx2 than SG8_30 strains, attention should also be paid to this SG.